2016
DOI: 10.1080/02626667.2016.1170131
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of numerical weather prediction based rainfall forecasts

Abstract: A.Seed@bom.gov.au +61 39669 4591 (A. Seed), P.Steinle@bom.gov.au +61 39669 4848 (P. Steinle) Abstract Assessment of the forecast precipitation is required before it can be used as input to hydrological models. Using radar observations in south-eastern Australia, forecast rainfall from the Australian Community Climate Earth-System Simulator (ACCESS) is evaluated for 2010 and 2011. Radar rain intensities were first calibrated to gauge rainfall data from four research rainfall stations at hourly time steps. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…For instance, the radar station can be used to generate rainfall field nowcasts (<6 h) by means of analogues (inferring from historical records), which can directly benefit flash flood forecasting [109]. Remotely sensed precipitation estimates can also be used to improve rainfall forecasts, e.g., assimilated into numerical weather prediction (NWP) models, to improve operational flood forecasting [110,111]. Those topics should draw more attention in the hydrologic forecasting community.…”
Section: Remotely Sensed Precipitation For Rainfall Forecastmentioning
confidence: 99%
“…For instance, the radar station can be used to generate rainfall field nowcasts (<6 h) by means of analogues (inferring from historical records), which can directly benefit flash flood forecasting [109]. Remotely sensed precipitation estimates can also be used to improve rainfall forecasts, e.g., assimilated into numerical weather prediction (NWP) models, to improve operational flood forecasting [110,111]. Those topics should draw more attention in the hydrologic forecasting community.…”
Section: Remotely Sensed Precipitation For Rainfall Forecastmentioning
confidence: 99%
“…Timing errors for system using short lead-time forecast may result in the pre-storm release being too late to reduce overflow, but this will have much lower impact for long forecast lead-time strategies, such as S1 Flood Protection. More importantly, error in rainfall intensity is the main source of forecast uncertainty, especially on the daily time scale (Shahrban et al, 2016). Over-prediction causes unnecessary release leading detriment to reductions in yield.…”
Section: Forecast Errormentioning
confidence: 99%
“…Therefore, improving the accuracy of precipitation forecast is an effective way to improve the accuracy of hydrological forecast. Many studies have shown that numerical weather prediction (NMP) and climate models can improve the skills of precipitation forecast significantly [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%